hsa-miR-9-5p-Mediated TSPAN9 Downregulation Is Positively Related to Both Poor Hepatocellular Carcinoma Prognosis and the Tumor Immune Infiltration - Shengkui Tan; Xin Song; Chenchen Zhang; Yishu Sun; Jiaxi Zhang; Zhongqi Zhang; Rongcheng Zhang; Tianmiao Zhang; Xiaonian Zhu; Hongzhuan Tan (Journal of Immunology Research)
Tetraspanins (TSPANs) play crucial roles in cell adhesion, migration, and metastasis of human cancer. However, there is no study in revealing the aspects of TSPAN9 traits and its functions in hepatocellular carcinoma (HCC) prognosis. Our study is the first to portray the TSPAN9 expression in HCC tissues with immunohistochemistry (IHC) analysis. Subsequently, a series of bioinformatics analyses such as expression estimation, survival assessment, and correlation analysis were implemented to dig out the possible upstream noncoding RNAs (ncRNAs) for TSPAN9 in HCC. In this way, the relevance within TSPAN9 and tumor immunity was then explored. We found that the TSPAN9 was downregulated in HCC tissues and had a correlation with HCC prognosis. Furthermore, we identified that the AL139383.1-hsa-miR-9-5p axis was the upstream ncRNA-related pathway most associated with TSPAN9 in HCC. Besides that, expression of TSPAN9 held a significantly negative correlation with tumor immunocyte infiltration as well as immune checkpoint CTLA4. TSPAN9-related immunomodulators were mainly enriched in T cell activation, leukocyte cell-cell adhesion, regulation of T cell activation, and regulation of leukocyte cell-cell adhesion signaling pathway. In conclusion, our results indicated that hsa-miR-9-5p-mediated downregulation of TSPAN9 was associated with poor HCC prognosis, immune-related signaling pathway, and tumor immune infiltration.